Are the poor too poor to demand health insurance? - Rajeev Ahuja; Johannes Jütting (Indian Council for Research on International Economic Relations (ICRIER), 2004)
Community based micro insurance has aroused much interest and hope in meeting health care challenges facing the poor. In this paper we explore how institutional rigidities such as credit constraint impinge on demand for health insurance and how insurance could potentially prevent poor households from fallinginto poverty trap. In this setting, we argue that the appropriate public intervention in generating demand for insurance is not to subsidise premium but to remove these rigidities (easing credit constraint in the present context). Thus from insurance perspective as well, our analysis highlights the importance of having appropriate savings and borrowing instruments for the poor.
Keywords: 330; Micro-insurance; Micro-credit; Credit Constraint; Demand for Insurance; Armut; Krankenversicherung; Soziale Sicherheit; Entwicklungsländer; Mikrofinanzierung